Linear Perspective and Framing in the Vista Paradox. (November 2017) - Costa, Marco; Bonetti, Leonardo
The vista paradox is the illusion in which an object seen through an aperture appears to shrink in apparent size as the observer approaches the aperture. In four studies, we tested the effect of framing and fixating on the target object. The first two studies assessed the vista paradox in a large scale naturalistic setting in which a 162.26 -m long corridor was aligned to a 97.2 -m high tower (1, 407 m away). In the first study, the results showed, for each 16 m section, a mean 9.95% tower enlargement in the moving backward condition, and a mean 11.62% shrinking in the moving forward condition. In the second study, participants had to compensate perceived width change adjusting the focal length of a photographic zoom lens. The results showed, for each 16 m section, a mean change in optical size of 26.37% in the experimental condition, and of 53.08% in the control condition. In the third study, we presented an identical vertical rectangle inserted within five frames differing in size. In the fourth study, linear perspective was added to the images. The results showed that both frame size and linear perspective cues were critical factors for the vista paradox illusion.